Konsep Pendidikan Berdasarkan Nilai-Nilai Al-Qur’an Surat Annahl Ayat 125 - Siti Mardiana; Paisal Paisal (EL-EMIR Institute, 2026)
Islamic education plays a crucial role in shaping the character, morals, and spirituality of students amidst increasingly complex developments. However, the current Islamic Religious Education learning process still faces various challenges, such as a decline in students' morals, a lack of role models, and theoretical learning methods. Therefore, an educational concept based on the Qur'an is needed as the primary guideline for learning. This study aims to determine the educational concept based on the Qur'anic values ​​in Surah An-Nahl, verse 125, and analyze its implementation in Islamic Religious Education learning strategies. This study used a qualitative approach with library research. Data were obtained from the Qur'an, tafsir books, hadith, books, and relevant scientific journals, then analyzed using content analysis. The results show that Surah An-Nahl, verse 125, contains three main principles of Islamic education: wisdom, mau'izhah hasanah, and mujadalah billati hiya ahsan. These three principles can be implemented through humanistic learning strategies, role models, interactive dialogue, and moral development, thereby developing students who are knowledgeable, have noble morals, and possess Islamic personalities.